Cord blood banks: Current challenges and vision - Δάφνη (Christina Dafni), Χριστίνα; Πεφάνης (Nikolaos Pefanis), Νικόλαος; Δήμου (Danai Dimou), Δανάη; Πούλος (Georgios Poulos), Γεώργιος; Ιωαννίδου (Anna Maria Ioannidou), Άννα Μαρία; Κατσίλα (Theodora Katsila), Θεοδώρα; Πατρινός (Giorgos Patrinos), Γεώργιος (Bioethica, 2017)
Stem cell transplants have been proved beneficial toward optimum disease management. In particular, cord blood has been a valuable source of stem cells with clinically proven applications for the treatment of a series of heamatological and immune system malignancies and several genetic disorders. To this end, cord blood banking has been established in the public and private sector. Nevertheless, current morals and ethics as well as the lack of a well-defined legal framework for the operation of cord blood banks hamper their clinical role and concern the general public.